Migraciones, inmigraciones y derechos humanos: un horizonte de acción para el Trabajo Social - Maritza Carolina Jaimes Márquez; Juan Carlos Chaparro Rodríguez; Laura Nataly Galvis Velandia (Mundo Fesc)
This study aims to compare student perceptions of two contemporary teaching methodologies: online learning and flipped learning. It focuses on how these approaches influence the acquisition of key competencies in the educational process. A quasi-experimental methodology with a pretest-intervention-posttest design was implemented in a sample of university students, seeking to comprehensively assess differences in learning dimensions, competencies developed, and final grades. The results show a significant correlation between the application of online and flipped learning methods and improvements in academic performance. It was evident that the fusion of both approaches promotes a positive effect on educational experiences, self-assessment, and knowledge acquisition, without one clearly standing out over the other. The study underscores the importance of properly integrating technology into education, highlighting flipped learning as an ideal starting point for novice students, due to its effectiveness in linking theory and practice, before moving on to online learning, which allows for greater autonomy. He acknowledges the limitations of his results due to the small sample used, but finds them promising, recommending future research with larger and more diverse groups to confirm and expand the applicability of these educational methodologies.